2016
DOI: 10.18410/jebmh/2016/583
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Lipid Profile and Prevalence of Microvascular Complication in Type 2 Diabetes Mellitus Patients: A Hospital Based Study

Abstract: To evaluate the prevalence and microvascular complication of type 2 diabetes mellitus patients. METHODOLOGY A detailed history, clinical examination and investigative procedure were used. RESULTS Pearson correlation coefficient, t-test and Fisher exact test were applied for statistical analysis. And P value was taken less than 0.05 for significant differences. Conclusions: Microvascular complication was more common in higher age group patients; its prevalence was 39%. And dyslipidaemia was present in 36% patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Prevalence of diabetes is known increase with age and similar finding have been reported by other studies. 14,16,17 The mean duration of diabetes in our study population was 6.34 years for euthyroid and 6.26 years for hypothyroid patients. The mean HbA1c (%) of our study population ranged from 5.2 to 17% and median of 7.84%, which is comparable to studies done earlier.…”
Section: Resultsmentioning
confidence: 92%
“…Prevalence of diabetes is known increase with age and similar finding have been reported by other studies. 14,16,17 The mean duration of diabetes in our study population was 6.34 years for euthyroid and 6.26 years for hypothyroid patients. The mean HbA1c (%) of our study population ranged from 5.2 to 17% and median of 7.84%, which is comparable to studies done earlier.…”
Section: Resultsmentioning
confidence: 92%
“…Above studies[ 7 8 9 10 11 12 13 14 15 16 17 18 19 ] showed that age, duration of diabetes, dyslipidemia, glycated hemoglobin, microvascular complications, macrovascular complications, and alcoholic status are risk factors for the development of PN.…”
Section: N Europathy R Elated To mentioning
confidence: 99%